Relationships between oral infections and blood glucose concentrations or HbA1c levels in normal and diabetic rats - Cintra, L. T.A. [UNESP]; Samuel, R. O. [UNESP]; Facundo, A. C.S. [UNESP]; Prieto, A. K.C. [UNESP]; Sumida, D. H. [UNESP]; Bomfim, S. R.M. [UNESP]; Souza, J. C. [UNESP]; Dezan-Júnior, E. [UNESP]; Gomes-Filho, J. E. [UNESP] (Wiley, 2014)
Aim: To measure glycosylated haemoglobin (HbA1c) in a diabetic model as a means of investigating apical periodontitis and periodontal disease for their effects on both blood glucose concentrations and long-term glycaemic control. Methodology: Wistar rats (n = 80) were assigned to one of eight groups (10 animals/group): control (G1), apical periodontitis (G2), periodontal disease (G3), apical periodontitis and periodontal disease (G4), diabetic (G5), diabetic with apical periodontitis (G6), diabetic with periodontal disease (G7) and diabetic with apical periodontitis and periodontal disease (G8). A diabetic state was induced with streptozotocin. Apical periodontitis was induced by dental exposure to the oral environment. Periodontal disease was induced by periodontal ligature. Blood glucose concentrations were measured at 0, 6, 30 and 60 days. After euthanization, rat maxillae were excised and processed for histopathology and for measurement of HbA1c levels by ion exchange chromatography. Data were tabulated and subject to statistical analysis (P < 0.05). Results: The inflammatory infiltrate and alveolar bone resorption were more severe in diabetic rats (P < 0.05). Diabetic rats exhibited higher levels of HbA1c independent of apical periodontitis or periodontal disease (P < 0.05). However, the presence of oral infections in diabetic rats was associated with increased blood glucose concentrations (P < 0.05). Conclusions: Oral infections affect glycaemic conditions in diabetic rats and increase HbA1c levels in normoglycaemic or diabetic rats. © 2013 International Endodontic Journal.
Keywords: Blood glucose; Diabetes; HbA1c levels; Oral infections